THE ROLE OF THE NEWEST HISTORY OF UZBEKISTAN IN THE EDUCATION OF YOUTH IN THE SPIRIT OF PATRIOTISM (ON THE EXAMPLE OF HIGHER EDUCATIONAL INSTITUTIONS) - Makhmanazarov Kahramon Abdiyevich (American Journals, 2026)
This scientific article analyzes the role of the course “The Contemporary History of Uzbekistan” in fostering patriotism among students in higher education institutions. The study highlights the significance of political, socio-economic, and spiritual reforms carried out during the independence period in shaping national pride, historical memory, and loyalty to the homeland among young people. The article substantiates the educational potential of this discipline in developing students’ civic responsibility, social engagement, and national identity.
Keywords: Patriotic education, contemporary history of Uzbekistan, higher education, national pride, historical memory, youth.